Higher Ki67 expression in fibroblast like cells at invasive front indicates better clinical outcomes in oral squamous cell carcinoma patients - Jing, Yue (Biosci Rep, 2018)
Background: Ki67 has been a key role for the treatment options and prognosis evaluation in some kinds of tumors; however, the spatial expression of Ki67 in oral squamous cell carcinoma (OSCC) has not been fully-evaluated. Therefore, in the present study, we aimed to elucidate the prognosis value of Ki67 spatial expression including in different cell types and at different compartments of tumor in OSCC patients. Methods: Immunohistochemical expression of Ki67 in tumor cells (TCs) and fibroblast like cells (FLCs) at center of tumor (CT) and invasive front (IF) was evaluated in 109 OSCC patients. Then correlations of Ki67 expressions with clinicopathological parameters were analyzed by Chi-square test, and survival curves were evaluated by Kaplan–Meier methods. Furthermore, univariate and multivariate analysis were performed to assess the diagnostic values of Ki67 expression by the Cox regression model. Results: Ki67 expression in TCs was much higher than in FLCs both at CT and IF compartments, but Ki67 expression in TCs was simultaneously higher at CT than that at IF (P=0.0004), which was converse to Ki67 expression in FLCs (P<0.0001). Additionally, high Ki67 expression in FLCs at IF was significantly associated with poor tumor differentiation (P=0.003), worse depth of invasion (DOI, P=0.027) and worst pattern of invasion (WPOI, P=0.041), but Ki67 expression in TCs had no correlation with clinical parameters no matter at CT or IF. Moreover, patients with higher Ki67 expression in TCs at CT had significantly increased risk for OS (overall survival; HR:1.935, 95% CI: 1.181–4.823, P=0.0395) and DFS (disease-free survival; HR: 2.974, 95% CI:1.189–5.023, P=0.046). On contrary, higher Ki67 expression in FLCs at IF was correlated with better OS (HR: 0.15, 95% CI: 0.018–0.846, P=0.0396) and DFS (HR: 0.15, 95% CI: 0.018–0.947, P=0.0445). Whereas, Ki67 expression both at TCs in IF and at FLCs in CT had no significant prognostic value for OS and DFS. Furthermore, Cox multivariate analysis revealed that Ki67 expression in FLCs at IF could not be an independent prognostic factor for OSCC patients. Conclusion: These results show that higher Ki67 expression in FLCs at IF indicated better clinical outcomes for OSCC patients.